DAMPAK SOSIALISASI BAHAYA MEROKOK DAN IMPACT DALAM BERMEDIA SOSIAL TERHADAP PENGETAHUAN DAN SIKAP SISWA SMKN 1 GRATI - Maulidya, Chindy; Shahvithri, Noureel Alya; Zakiyah, Ermita (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine students' perspectives on the dangers of smoking and the impact of social media on the knowledge and attitudes of students of SMKN 1 Grati. This is based on the phenomenon of adolescent recognition being one of the inevitable things in the growth and development of students. The population in this study were students of SMK 1 Grati. The sampling technique in this study used incidental sampling technique as many as 87 students. Teenagers aged 15-18 years are generally still vulnerable to the phenomenon of juvenile delinquency, one of which is smoking. The friendship environment and the use of social media are determinants in carrying out these actions. Unwise use of social media allows for higher rates of juvenile delinquency in Indonesia. Through a quantitative approach, all data were processed using IBM SPSS 25 and collected through questionnaires. The results showed a difference in the perspective of students of SMKN 1 Grati before and after socialization.